2021
DOI: 10.1016/j.jctube.2021.100220
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic implications and inpatient mortality related to tuberculosis at Jimma Medical Center, southwest Ethiopia

Abstract: Background Tuberculosis (TB) is one of the major public health problems in Ethiopia. Determining discharge outcome of TB cases helps to understand the effectiveness of TB diagnosis effort to improve case management. The objective of this study was to assess discharge outcomes and factors associated with death among patients on TB treatment admitted in a referral hospital in southwest Ethiopia. Methods A retrospective study was conducted in Jimma Medical Center by review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Other studies in Malawi and Zimbabwe reported mortality rates of 23% and 22%, respectively [41,42]. A review by Kebede et al [43] in Ethiopia also had a lower mortality rate of 24.5% in a hospital-based review of TB cases. Comparatively, the later study had a lower HIV population of 27% with only 18% of them diagnosed with EPTB while our cohort had 34% HIV cases with 49% of them diagnosed with EPTB.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies in Malawi and Zimbabwe reported mortality rates of 23% and 22%, respectively [41,42]. A review by Kebede et al [43] in Ethiopia also had a lower mortality rate of 24.5% in a hospital-based review of TB cases. Comparatively, the later study had a lower HIV population of 27% with only 18% of them diagnosed with EPTB while our cohort had 34% HIV cases with 49% of them diagnosed with EPTB.…”
Section: Discussionmentioning
confidence: 84%
“…We obtained a mortality rate of 10.2%, but in different studies [ 17 ], it varies greatly [ 18 ]. There is no significant difference in terms of mortality between those who receive the diagnosis during admission or before admission.…”
Section: Discussionmentioning
confidence: 99%
“…The grade of the smear is determined by the bacillary load in each microscopic field. Some studies have found that the grade of primary smear can be considered as a predictive factor of patient's morbidity and mortality, which, in the case of a higher grade of positivity, it is more likely to be a failure in treatment and cause death [7,18]. In some studies, the relationship between the grade of primary positive smear and increased clinical manifestations has been stated [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chest X-ray is also a suitable and sensitive diagnostic tool for detecting pulmonary lesions, including in tuberculosis, so that in the case of a normal chest X-ray, the diagnosis of tuberculosis is partially excluded [8,12]. On the other hand, in cases where this disease is actively sought, and when it is diagnosed at an early stage, pulmonary involvement can be a sign of our success in the early detection of these patients, resulting from radiographic findings [7]. Based on the researcher's best knowledge there is no study has been conducted to investigate the relationship between the findings of chest X-ray radiography and the grade of positivity of sputum smear in Iran and especially Southeast of Iran as an area with a high prevalence of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%